Combien vaut notre entreprise? - Guy, Paul (Relations industrielles / Industrial Relations, 1968)
This article reviews "Combien vaut notre entreprise?" by André Barnay and Georges Calba.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z